2021
DOI: 10.1097/psy.0000000000000956
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Somatic Symptoms in School Refusal

Abstract: Objective: School refusers often display somatic symptoms that are temporally related to school attendance. The aim of this systematic review is to summarize characteristics and causes of somatic symptoms and their management in the context of school refusal. Findings of this review may help clinicians in their daily practice. Methods: PubMed and PsycINFO databases were systematically searched (according to PRISMA guidelines) for articles mentioning somatic symptoms in school refusal by May 2020. Among 1025 id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 177 publications
2
16
0
Order By: Relevance
“…Meanwhile, it is partially consistent with the opinions of attachment theory that the emotional instability of caregivers is correlated with children's uncertainty and insecure attachment experience and related to more psychosomatic complaints among children ( 32 ). As implied by Li et al's ( 33 ) study, school refusers often display somatic symptoms including headache, abdominal pain, vomiting, nausea, dizziness, diarrhea, muscular ache, fatigue and palpitation, and anxiety was found to be the most recurrent etiology of those somatic complains. Moreover, prior studies have also suggested that children's school refusal is correlated with their interpersonal conflicts, their enmeshment with their parents and parental psychopathology ( 9 , 13 , 14 , 16 ).…”
Section: Discussionmentioning
confidence: 90%
“…Meanwhile, it is partially consistent with the opinions of attachment theory that the emotional instability of caregivers is correlated with children's uncertainty and insecure attachment experience and related to more psychosomatic complaints among children ( 32 ). As implied by Li et al's ( 33 ) study, school refusers often display somatic symptoms including headache, abdominal pain, vomiting, nausea, dizziness, diarrhea, muscular ache, fatigue and palpitation, and anxiety was found to be the most recurrent etiology of those somatic complains. Moreover, prior studies have also suggested that children's school refusal is correlated with their interpersonal conflicts, their enmeshment with their parents and parental psychopathology ( 9 , 13 , 14 , 16 ).…”
Section: Discussionmentioning
confidence: 90%
“…Absence due to illness applied to 34% of those with absence due to school withdrawal and 51% of those with absence due to school refusal. The high rate of co-occurring absence due to school refusal and illness likely reflects somatic symptoms in the presentation of school refusal (Li et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Many forms of school attendance/absenteeism exist across multiple instructional formats, including virtual or distance learning formats, that demand new and broader metrics (e.g., log-ins, completed assignments, student-teacher interactions, and mastery of skills) for measuring these constructs (National Forum on Education Statistics, 2021). In addition, school absenteeism comprises a spectrum of attendance problems that can include full or partial day absences, missing classes, tardiness, student/family problems in the morning, and distress, somatic complaints, and other psychological problems that interfere with school attendance (Li et al, 2021;Kearney and Gonzálvez, 2022). This has led to broader definitions of school attendance/absenteeism that focus less on physical presence/absence and more on engagement (Patrick and Chambers, 2020;Kearney, 2021).…”
Section: The Past: What Is Known?mentioning
confidence: 99%